ANALISIS PENGARUH STRUKTUR ORGANISASI TERHADAP KINERJA PROYEK PEMBANGUNAN JEMBATAN EMBUNG SUNGSANG - Desrimon, Arfi; Setiawan, Beny; Aisyah Ariad, Agrah; Akbar, Faisal; Ewaldo, M.Faith; Hayati, Misbah (Ensiklopedia Research and Community Service Review, 2024)
The performance of a project can be influenced by its organization. Good organizational management can help ensure that responsibilities and tasks are clearly divided among project team members, that communication is maintained well, and that the project can run according to schedule. Project management can also help organizations discover and resolve problems that arise during a project. An effective project organizational structure will achieve project objectives in accordance with the expected time, cost and budget. The aim of this research is to assist the project party in identifying problems that exist in the project organizational structure and also provide solutions related to problems that exist in the project structure. Meanwhile, the most influential is quality with a score of 3.42% greater than the time and cost indicators.Kata Kunci: organization, Management, Construction